(untitled) (Research, Society and Development, 2021)
The article aims to highlight the relevance of the young apprentice project as a way to insert young people into the labor Market. Society has been going through a big change in the ways of working and the way to get a job. When punctuating adolescence in the individual and social context, conceptualizing work and explaining about the labor market, it is necessary, in the Brazilian social economic scenario, to discuss the law of apprenticeship, the Young Apprentice Project. This brings the obligation for companies to hire young people, offering tax incentives; associates paid activity with methodical technical-professional qualification, contributing to the fight against social and economic problems, and to the life perspective of young people, including in the choice of professional practice area, as is the case of young people who worked in the Public Ministry who followed legal career.